Beten, Impfen, Sammeln Zur Viehseuchen- und Schädlingsbekämpfung in der Frühen Neuzeit Graduiertenkolleg Interdisziplinäre Umweltgeschichte - Engelken, Katharina; Hünniger, Dominik; Windelen, Steffi (Universitätsverlag Göttingen, 2007)
The collection covers the presentations held at the workshop on "Challenge: Securing Resources - Animal Diseases and Pest Control in the 18th and 19 Century" held in Goettingen on 21 and 22 June 2006 by the graduate school "Interdisciplinary Environmental History, Natual Environment and Society in Central Europe", which is funded by the German Research Foundation, and operative since July 1 2004 at the Georg-August University in Goettingen.